Novel thoracoscopic segmentectomy combining preoperative three-dimensional image simulation and intravenous administration of indocyanine green. (3rd March 2022) - Matsuura, Natsumi; Igai, Hitoshi; Ohsawa, Fumi; Numajiri, Kazuki; Kamiyoshihara, Mitsuhiro
Abstract: OBJECTIVES: The aim of this study is to assess prospectively the validity and feasibility of segmentectomy using preoperative simulation and intravenous indocyanine green (ICG) with near-infrared (NIR) light thoracoscope to ensure a sufficient surgical margin. METHODS: This study was a prospective, single-centre, phase II, feasibility study. From February to July 2021, 20 patients were enrolled in this study. All patients underwent preoperative three-dimensional computed tomography angiography and bronchography using simulation software. The dominant pulmonary artery of the targeted segment was selected to determine the dissection line and measure the surgical margin to the tumour. Intraoperatively, after the planned dissection of the pulmonary artery, ICG (0.3 mg/kg) was administered intravenously and observed with NIR, and dissection was performed along the line determined by preoperative simulation. Postoperatively, the pathological margin was compared with the simulation margin. RESULTS: All surgeries were performed via an uniport (3.5–4.0-cm skin incision). The regions of segmentectomy were S2, S3, S6, S9 + 10 and S10 of the right side and S1 + 2 + 3, S3, S3 + 4 + 5, S6 and S8 of the left side. The difference between the simulation margin and the pathological margin was not significant (simulation 30.5 ± 10.1 vs pathological 31.0 ± 11.0 mm, P  = 0.801). The simulation margin was well correlated with the pathological margin ( R 2 = 0.677). The proportion of cases successfully achieving the pathological margin of error of plus or minus 10 mm of the simulation margin was 90% (18 of 20 cases). CONCLUSIONS: The combination of preoperative three-dimensional computed tomography simulation and ICG–NIR was effective for securing a sufficient margin in segmentectomy. Abstract : Although the standard radical surgery for primary lung cancer is still lobectomy [1], an early-stage non-small-cell lung cancer with ground-glass opacity (GGO) on thin-section computed tomography (CT) has been shown to have a very good prognosis, and segmentectomy has become widespread [2–5].